2003
DOI: 10.1002/ptr.1130
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic and hypolipidaemic action of alcohol extract of Tinospora cordifolia roots in chemical induced diabetes in rats

Abstract: The present investigation was undertaken to evaluate the hypoglycaemic and hypolipidaemic effects of an alcohol extract of Tinospora cordifolia roots, an indigenous plant used in Ayurvedic medicine in India. Oral administration of the extract of Tinospora cordifolia (TCREt) roots for 6 weeks resulted in a significant reduction in blood and urine glucose and in lipids in serum and tissues in alloxan diabetic rats. The extract also prevented a decrease in body weight. Thus our study clearly shows that an alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…According to the Ayurvedic System of Medicine, T. cordifolia is an antigout, analgesic, rejuvenator, astringent, anthelmintic, antiarthritic, antiperiodic, antipyretic, antimalarial, antiinflammatory, aphrodisiac, antiasthmatic, bitter tonic, carminative, cardiotonic, constipative, digestant, diuretic, blood purifier, expectorant, antidiabetic, antigonorrhoeal, cholagogue, antiemetic and antiicteric5–7. T. cordifolia has been claimed to possess learning and memory enhancing8, antioxidant9, antiischemic10, hypolipidaemic11, antidiabetic12, antiulcer13, hepatoprotective14, antifertility15, antiinflammatory16, antiallergic17, immunomodulatory18, anticancer19 and radioprotective20. The chemical constituents of T. cordifolia stems include alkaloids like berberine, palmatine, tembetarine, magnoflorine2122, glycosides like tinocordiside23, tinocordifolioside, cordioside24, cordifolioside A, B25, cordifoliside A, B, C, D, E2627, steroids like ecdysterone, makisterone A, giloinsterol28, sesquiterpenoids like tinocordifolin29.…”
mentioning
confidence: 99%
“…According to the Ayurvedic System of Medicine, T. cordifolia is an antigout, analgesic, rejuvenator, astringent, anthelmintic, antiarthritic, antiperiodic, antipyretic, antimalarial, antiinflammatory, aphrodisiac, antiasthmatic, bitter tonic, carminative, cardiotonic, constipative, digestant, diuretic, blood purifier, expectorant, antidiabetic, antigonorrhoeal, cholagogue, antiemetic and antiicteric5–7. T. cordifolia has been claimed to possess learning and memory enhancing8, antioxidant9, antiischemic10, hypolipidaemic11, antidiabetic12, antiulcer13, hepatoprotective14, antifertility15, antiinflammatory16, antiallergic17, immunomodulatory18, anticancer19 and radioprotective20. The chemical constituents of T. cordifolia stems include alkaloids like berberine, palmatine, tembetarine, magnoflorine2122, glycosides like tinocordiside23, tinocordifolioside, cordioside24, cordifolioside A, B25, cordifoliside A, B, C, D, E2627, steroids like ecdysterone, makisterone A, giloinsterol28, sesquiterpenoids like tinocordifolin29.…”
mentioning
confidence: 99%
“…The antioxidant activity of the extract may also be due to the presence of these alkaloids. In our earlier study we have shown that aqueous TCREt exhibits antioxidant activity (Stanely Mainzen Prince and Menon, 2003). In this communication, the alcoholic extract of TCREt was observed to have antioxidant effects, but the alcoholic extract showed a better effect than the aqueous extract and normalized all the parameters in alloxanized diabetic rats.…”
Section: Resultsmentioning
confidence: 89%
“…Hence, we measured the lipid profile in the serum (total, LDL, non-HDL, and HDL cholesterol and triglycerides) and free fatty acid along with the LDL to HDL ratio and our results suggest prominent hypolipidemic effect for G-400. This effect was the consequence of the synergic effect of G-400 constituents as evident from early study of S. oblonga (Bhat et al, 2012), G. sylvestre (Daisy et al, 2009), T. cordifolia (Stanely Mainzen Prince andMenon, 2003), E. officinalis (Augusti et al, 2001) and C. longa (Babu and Srinivasan, 1997).…”
Section: Discussionmentioning
confidence: 99%